Evaluation of Extension Reforms in Brazil - International Food Policy Research Institute; State University of Campinas; Federal University of São Carlos; Global Forum for Rural Advisory Services; Latin American Network for Rural Extension Services (International Food Policy Research Institute, 2018)
To evaluate the impacts of the rural extension policy (PNATER), five territories were selected in three different Brazilian states, including Alto Jequitinhonha (Minas Gerais State), Cantuquiriguaçu (Paraná State), Pontal do Paranapanema (São Paulo State), São Paulo’s Southwestern (São Paulo State), and Vale do Ribeira (Paraná State). An indicator system was elaborated to collect and analyze data from farmers and extension agents in each territory. 12 indicators were proposed to accomplish the desired evaluation. These indicators express the meaningful aspects of the extension reform policy document’s values, principles, and objectives. Data collection instruments were composed of questionnaires focusing on objective questions, allowing only closed answers to identify the interviewee’s perception of his or her reality. The possibilities for responses were elaborated on a five-point Likert scale—from the least to the greatest—asking respondents to indicate how much they agree or disagree, approve or disapprove, or believe to be true or false. The questionnaire for family farmers was composed of 56 questions, encompassing different indicators, among which three were specific for black rural and indigenous communities. The researchers also added questions from the Brazilian Food Insecurity Scale. In total researchers conducted 1,000 interviews with farmers and 87 interviews with extensionists (in some territories the goal of 20 interviews with the extensionists in each territory was not achieved due to the difficulty in contacting them or their unavailability in the study period) in the five territories between August 2014 to January 2015.